Body image perception and body composition in early adolescents: a longitudinal study of an Italian cohort - Stefania Toselli; Alessia Grigoletto; Luciana Zaccagni; Natascia Rinaldo; Georgian Badicu; Wilhelm Robert Grosz; Francesco Campa (BMC, 2021)
Abstract Background Adolescence is a sensitive period of life in which everyone faces physical and psychological changes. No longitudinal studies considering changes in body image perception and body composition in Italian adolescents have been carried out. The aims of this study were to evaluate the longitudinal change in body composition and weight status in a sample of Italian students of both sexes over the 3 years of middle school and to analyse the influence of these parameters on the perception and satisfaction of one's own body image. Methods Sixty-four males and seventy females were followed longitudinally from 11 to 14. Age at first measurement was 11.8 ± 0.3 yrs. in males and 11.9 ± 0.3 yrs. in females, then the students were measured again after 1 year and 2 years. Anthropometric measurements were collected and body composition was assessed by skinfolds. Maturity status was detected by age at menarche in females and by estimated age at peak height velocity in males; sports practice was assessed by a questionnaire. Body Silhouette Charts were used to assess body image perception. The degree of body image dissatisfaction and improper perception of weight status were evaluated. Univariate and multivariate analyses were applied. Results Height, sitting height, leg length, and weight increments were higher in males than in females, and in both sexes the sitting height increment was higher than that of leg length. Skinfold thicknesses and percentage of body fat, showed a decrease in males and an increase in females over the 3 years. About 90% of the sample practiced sport during the 3 years. No significant variations in body image perception were observed among repeated measures but significantly differences were observed between sexes. Although the girls showed a lower incidence of overweight and obesity than boys, girls had a higher dissatisfaction than males. Males were less accurate in one's perception of one's own weight status. Conclusions The changes in body composition observed in the sample of the present study were in accordance with their maturity stage. An increase in parameters connected with adiposity is observed in females and a decrease in males. Body image perception did not seem to change with growth, but associations were found between body image perception and BMI and sex. Monitoring body image perception in young adolescents, especially in females and in overweight/obese subjects, is a priority to prevent nutritional disorders.